The Instrumentalization of Religion in Identity Politics: A Fiqh Siyasah Theory Perspective Ahead of Elections in Contemporary Muslim Society - Firman Robiansyah; Amanda Nurul Febrilian; Linda Arfryanti; Zahrotul Hayat (Universitas Negeri Semarang, 2026)
The phenomenon of religious instrumentalization in identity politics ahead of the election is becoming an increasingly relevant issue in contemporary Muslim society. The use of symbols, narratives, and religious sentiments in political contestation often no longer functions as a means of moral education, but as an instrument of electoral mobilization that has the potential to trigger social polarization. This research aims to analyze the practice of religious instrumentalization in identity politics ahead of the election through the perspective of fiqh siyasah and examine the relevance of fiqh siyasah principles in modern democracy. The research uses a descriptive qualitative method with a literature study approach that examines various scientific literature, books, and articles related to identity politics, religious politicization, and fiqih siyasah. The novelty of this research lies in the effort to integrate the principles of classical and contemporary fiqh to evaluate the practice of identity politics in the context of modern democracy. The results of the study show that the use of religion as a tool for political legitimacy is contrary to the principle of justice (al-'adl), deliberation (asy-shura), trust, and benefit which is the basis of the syar'iyyah siyasah. This practice has the potential to shift democracy from the arena of exchanging ideas into an identity conflict that divides society. This research emphasizes the importance of strengthening political literacy, digital literacy, and moderate religious understanding to maintain the function of religion as a source of public ethics and social adhesive. The implication of this research is expected to be a reference for academics, religious figures, and policy makers in building a more inclusive and cultural political culture.